Navigating Complexity: Spontaneous Psoas Hematoma in MASLD Cirrhosis and Anticoagulation Therapy - Jameel Alp; Arianne K. Baldomero (Annals of Internal Medicine: Clinical Cases)
Spontaneous psoas hematoma is a rare but highly fatal complication of alcohol-associated cirrhosis. Most cases in the literature involve alcohol-related cirrhosis, particularly in Asian populations. We present a case of a 76-year-old White man with cirrhosis due to metabolic dysfunction-associated steatotic liver disease who developed a spontaneous psoas hematoma while on anticoagulation therapy for an extensive deep venous thrombus. Despite blood products and octreotide, his condition deteriorated. After timely discussions about goals of care, treatment shifted to focus on comfort. This case highlights the challenging balance between hypercoagulability and bleeding risk in cirrhosis and illustrates a rare complication.